A experiência subjetiva de pacientes com o uso medicinal da Cannabis sativa L. : uma revisão integrativa. - Cristiane Mendonça de Oliveira (2023)
Cannabis sativa L., for its various uses, has an extensive history related to social, economic and cultural issues. The debate about the use of cannabis as a medicine has been widespread, since it is an herb banned in many places in the world. Scientific research, despite having advanced in recent years, has left aside the approach of subjective experience with the medicinal use of this plant. Given this scenario, this study aims to demonstrate the subjective experience with the use of products based on Cannabis sativa L. For the development of this research, initially, a bibliographic review was carried out in the online databases to explore and comprehensively examine publications on the medicinal use of Cannabis, obtaining an overview of the knowledge involving this theme. Next, an integrative review of articles from primary sources that used qualitative methodology and that investigated the patient's experience in relation to the medicinal use of cannabis was structured. The three most recurrent themes, in descending order, were "Benefits of use", "Challenges faced" and "Contemporary usage patterns". The most cited subthemes in the first mentioned theme were "Perceived efficacy" and "Fewer unwanted effects and lower amounts of medications." In the second theme mentioned, the most expressive subtheme was "Medical disapproval and fear of talking to health professionals". Finally, in relation to the third theme mentioned, the subtheme "Varied methods of use" was the most recurrent. The results of this study can offer valuable information to practitioners, helping them to plan broader strategies in the process of teaching and research and to develop health practices more patient-centered.